Convergence of plasmid-mediated Colistin and Tigecycline resistance in Klebsiella pneumoniae - Zhao, Yujie; Qian, Changrui; Ye, Jianzhong; Li, Qingcao; Zhao, Rongqing; Qin, Ling; Mao, Qifeng (Frontiers in Microbiology, 2024)
Co-occurrence of colistin and tigecycline resistance genes in Klebsiella pneumoniae poses a serious public health problem. This study aimed to characterize a K. pneumoniae strain K82 co-harboring colistin resistance gene (CoRG) and tigecycline resistance gene (TRG), and importantly we also investigate genetic characteristics of the plasmid with CoRG or TRG in GenBank. K. pneumoniae strain K82 was subjected to antimicrobial susceptibility testing, conjugation assay, and wholegenome sequencing (WGS). In addition, comparative genomic analysis of CoRG or TRG-harboring plasmids from K82 and GenBank was conducted. K. pneumoniae strain K82 was resistant to all the tested antimicrobials including colistin and tigecycline except carbapenems. WGS and bioinformatic analysis showed that K82 belonged to the ST656 sequence type and carried multiple drug resistance genes including mcr-1 and tmexCD1-toprJ1, which located on IncFIA/IncHI2/IncHI2A/IncN/IncR-type plasmid pK82-mcr-1 and IncFIB/IncFII-type plasmid pK82-tmexCD-toprJ, respectively. The pK82-mcr-1 plasmid was capable of conjugation. Analysis of CoRG/TRG-harboring plasmid showed that mcr-8 and tmexCD1-toprJ1 was the most common CoRG and TRG of Klebsiella spp., respectively. These TRG/CoRG-harboring plasmids could be divided into two categories based on mash distance. Moreover, we found a IncFIB/IncHI1B-type plasmid pSYCC1_tmex_287k co-harboring mcr-1 and tmexCD1-toprJ1. To the best of our knowledge, this is the first report on the co-occurrence of mcr-1 and tmexCD1-toprJ1 on a single plasmid. Our research expands the known diversity of Co RG and TRG-harboring plasmids in K. pneumoniae. Effective surveillance should be implemented to assess the prevalence of co-harboring CoRG and TRG in a single K. pneumoniae isolate or even a single plasmid.